Leveraging smart glasses for telemedicine to improve primary healthcare services and referrals in a remote rural district, Kingandu, DRC, 2019–2020 - Jules Diaka; Wim Van Damme; Felipe Sere; Lenka Benova; Willem van de Put; Steven Serneels (Global Health Action)
Background Telemedicine enables new forms of medical consultation and is expanding worldwide. Patients in sub-Saharan Africa could potentially benefit substantially from telemedicine. Objective To improve primary healthcare services, especially referrals to the district hospital, for the population in three health centres in the rural district Kingandu in the Democratic Republic of the Congo (DRC) by introducing Smart Glasses, and leveraging them for telemedicine. Methods The project involved the design and introduction of an intervention combining community engagement with technological innovation (Smart Glasses, communication equipment, moto-ambulances, and new diagnostic tests), and with staff training. Utilisation of the intervention, use of the health centres, and referrals to the hospital were monitored through the routine health information system and project-specific registers. Key stakeholders were interviewed and the project costs were analysed. Results The use cases for the intervention were defined in consultation with the stakeholders. Smart Glasses were used in 10% of consultations in the health centres mostly for advice during curative consultations. The total number of consultations increased significantly in the intervention health centres. The number of referrals to the hospital remained stable, but an increased proportion effectively arrived in the hospital. The Smart Glasses and moto-ambulance greatly facilitated emergency referrals, often requiring a potentially life-saving intervention in the hospital. All stakeholders involved highly valued the intervention. Conclusion Telemedicine can contribute to improving primary healthcare services in a remote rural area, as part of a more comprehensive intervention and with intensive participation of all stakeholders. It can increase acceptability and use of the existing services; improve diagnosis, treatment, and referral of patients; and can also facilitate on-the-job training and supportive supervision.